Real-time implementation of H∞ controller for UAV helicopter using MATLAB-based embedded programming approach - Tijani, Ismaila; Akmeliawati, Rini; Legowo, Ari (IEEE, 2015)
The rapid-prototyping and deployment of flight control algorithm on a real-time embedded target has been one of the major challenges in an unmanned helicopter system development. In this paper, a MATLAB-Simulink based embedded target programming approach is presented to address this challenge. The motivation for this approach is that, since most of the computational tasks in the unmanned helicopter system, such as modeling, controller design and simulation are readily and effectively achieved within the MATLAB environment, then, extending the platform to deployment of the resulting flight algorithm onto an embedded target would greatly ease the overall developmental activities. The design and deployment of an H∞ based flight control algorithm onto an embedded target is presented for a small scale unmanned helicopter system. The results of the hardware-in-loop simulation and real-flight tests show effectiveness of the proposed approach. This is expected to facilitate and contribute towards a single-platform integrated development environment for unmanned system development.